Complete casting handbook : metal casting processes, metallurgy, techniques and design - Campbell, John, 1938- (Elsevier Butterworth-Heinemann, 2011)
"Complete Casting Handbook is the result of a long-awaited update, consolidation and expansion of expert John Campbell's market-leading casting books into one essential resource for metallurgists and foundry professionals who design, specify or manufacture metal castings."--P. [4] of cover.